DOES THE ADDITION OF DEXAMETHASON TO LOCAL ANESTHETIC PROLONG THE ANALGESIA OF INTERSCALEN PLEXUS BRACHIALIS BLOCK IN PATIENTS WITH SHOULDER SURGERY? - Nancheva Jasminka; Andonovski Alan; Georgieva Danijela; Bozinovski Zoran; Dzoleva Roza; Gavrilovski Antonio; Georgiev Antonio (Sanamed, 2016)
Abstract: Introduction: Peripherial nerve blocks is a suitable alternative to general anesthesia especially for one-day case surgery. Interscalene approach of plexus brachialis block as much as supraclavicular and infraclavicular provide reliable, safe, effective, low cost and most complete anesthesia with satisfactory postoperative analgesia for upper limb surgery. Postoperative analgesia of plexus brachialis blocks can be prolonged by using different drugs as adjuvants with local anesthetics. Dexamethasone has been shown to prolong the duration of postoperative analgesia when given as an adjunct for peripheral nerve blocks. The investigation was randomized, prospective, double blinded and controlled study.